Desarrollo de aplicación con sensores de temperatura usando una versión del lenguaje java llamada javelin adecuada para el uso en microcontroladores que admiten esta tecnología - Valdivieso, Carlos (2010)
The Javelin Stamp Starter Kit is essentially a module that is programmed with Java language instructions from Sun Microsystems. The objective of this project is the development of programming and implementation for a system that allows temperature sensing, with a package of Java used on the Javelin Stamp. The project consists of two parts, one of software code that implements the Java programming language, and another of hardware that provides an intelligent control to a DS1620 temperature device that can work autonomously with a thermostat function. The hardware Javelin Stamp is a tool that allows the development of the project based on the Javelin Stamp module and programming in Java using its own libraries. Chapter III presents figures that demonstrate. Besides it show how integration is performed on both sides, the electronics hardware and software how to start programming in Java including examples for identifying the syntax and terms used, that is to be able to write code used in this project.